Study of the morphology of mixed municipal waste in Poland – analysis of research methods - Bień, Jurand (Instal, 2026)
The article presents a critical review and comparative analysis of mixed municipal waste morphology testing methodologies used in Poland, in light of the growing demands of climate policy and the circular economy. The starting point is the observation that, despite the increase in selective waste collection, the residual waste stream remains a significant decision-making challenge for municipalities and installations, and the lack of a uniform national standard limits the direct comparability of results between research campaigns. The paper summarizes and discusses four main approaches: the withdrawn PN-93/Z-15006 standard, the Jędrczak and Szpadt procedure (2006), the Atmoterm guidelines (2018), and the IOŚ-PIB (2021) framework. The analysis indicates that the discrepancies in results are primarily due to differences in sample mass and generation (including reduction), sieve configuration, treatment of the <10 mm fine fraction, and the degree of aggregation of the material fraction catalog. A unified approach was proposed by introducing a common methodological “core” (including controlled sample reduction, seasonality, transparent reporting of sieve fractions, and a consistent set of material fractions) and purpose-specific modules (e.g., a fuel or technology “on-line” module). This approach is intended to improve the quality of data for reporting, investment planning, and corrective actions in collection and recovery systems.